2022
DOI: 10.1002/tcr.202200128
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Crystal Orientation of Cathode for Advanced Lithium‐Ion Batteries: A Minireview

Abstract: Engineering crystal orientation has attracted widespread attention since it is related to the cyclability and rate performance of cathode materials for lithium‐ion batteries (LIBs). Regulating the crystal directional growth with optimal exposed crystal facets is an effective strategy to improve the performance of cathode materials, but still lacks sufficient attention in research field. Herein, we briefly introduce the characterization techniques and identification methods for crystal facets, then summarize an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…[8] To improve the electrochemical performance of NVPF, researchers have adopted several strategies, such as nanosizing, [9] carbon coating, [10] heterogeneous ion doping, [11] and tuning the crystal facet growth. [12] As previously reported in our work, [13] changes in the crystal structure could affect the morphology and electrochemical performance of NVPF. In addition, Yi et al [14] reported a strategy for controlling NVPF crystal structure by adjusting the pH, which can influence the surface energy, thereby changing the morphologies of NVPF from a 0D nanoparticle (alkaline environment) to a 3D cubic structure (acidic environment).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…[8] To improve the electrochemical performance of NVPF, researchers have adopted several strategies, such as nanosizing, [9] carbon coating, [10] heterogeneous ion doping, [11] and tuning the crystal facet growth. [12] As previously reported in our work, [13] changes in the crystal structure could affect the morphology and electrochemical performance of NVPF. In addition, Yi et al [14] reported a strategy for controlling NVPF crystal structure by adjusting the pH, which can influence the surface energy, thereby changing the morphologies of NVPF from a 0D nanoparticle (alkaline environment) to a 3D cubic structure (acidic environment).…”
Section: Introductionsupporting
confidence: 61%
“…To improve the electrochemical performance of NVPF, researchers have adopted several strategies, such as nanosizing, [ 9 ] carbon coating, [ 10 ] heterogeneous ion doping, [ 11 ] and tuning the crystal facet growth. [ 12 ] As previously reported in our work, [ 13 ] changes in the crystal structure could affect the morphology and electrochemical performance of NVPF. In addition, Yi et al.…”
Section: Introductionmentioning
confidence: 55%
“…The structure is an inherent factor that governs the properties of materials. [ 53 ] As mentioned above, the unsatisfactory cycling performance of cathodes with multielectron redox reactions is primarily attributed to irreversible distortion in the crystal structure. For instance, previous studies have reported the origin of the rapid structural decay of LE‐NMVP.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, interfacial design and crystal engineering that control lattice orientation have attracted attention as a key strategy for improving the performance of ASSBs. [19][20][21][22][23][24][25][26] Building the textured, epitaxial, and single crystalline systems is able to refine and disclose the interfacial behaviors of electrochemical mechanisms as well as to improve the durability and energy density of solid-state batteries. 27,28 Furthermore, significant adverse events at interface, one of the major obstacles to ASSBs, can be successfully suppressed by optimizing the orientation order of electrodes and SEs.…”
Section: Introductionmentioning
confidence: 99%